Beyond mean-field dynamics in open Bose-Hubbard chains - Witthaut, Dirk; Trimborn, F.; Hennig, H.; Kordas, Geōrgios; Geisel, T.; Wimberger, Sandro (Physical review. A, Atomic, molecular, and optical physics, 2011)
We investigate the effects of phase noise and particle loss on the dynamics of a Bose-Einstein condensate in an optical lattice. Starting from the many-body master equation, we discuss the applicability of generalized mean-field approximations in the presence of dissipation as well as methods to simulate quantum effects beyond mean field by including higher-order correlation functions. It is shown that localized particle dissipation leads to surprising dynamics, as it can suppress decay and restore the coherence of a Bose-Einstein condensate. These effects can be applied to engineer coherent structures such as stable discrete breathers and dark solitons.
Gesehen am 21.11.2022